(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article presents a comparative analysis of the effectiveness of several heuristic algorithms used to optimize the distribution of medical equipment in a crisis. The key approaches, including the genetic algorithm (GA), the particle swarm optimization algorithm (PSO), and the ant colony optimization algorithm (ACO), are considered, and the performance and accuracy of the problem are investigated. Based on the experiments, the advantages and limitations of each method are determined, and practical recommendations are formulated for choosing the appropriate algorithm, considering the scale of the problem and limited resources. The study's results improve the reliability and efficiency of decision-making in healthcare systems during emergencies.